Formation of management decisions regarding the reconstruction of the destroyed infrastructure of Ukraine - Viktoriia Bozhanova; Oleksandra Kononova; Anzhela Cherchata; Valerii Liubushkin (Економічний вісник Державного вищого навчального закладу Український державний хіміко-технологічний університет, 2024)
The state of force majeure conditions of doing business as a result of military events during 2022-2024 in Ukraine became a prerequisite for conducting a study based on the state of external environment of enterprises in the construction industry operating in such conditions. These conditions made it possible to determine their typical problems: shortage of financial resources for the reconstruction of the country’s destroyed infrastructure, loss of established partnerships, in particular among enterprises in the construction industry, shortage of production personnel, production capacities of enterprises may not meet market requirements, imperfection of approaches to assessing the ability of enterprises to be reliable business partners, insufficiency of factories, and mobile installations for industrial recycling of construction materials. This led to formulating the goal of this scientific study: the development of theoretical and methodological approaches to the formation of management decisions regarding the reconstruction of destroyed infrastructure in Ukraine. As a result, approaches that have been developed regarding to the management tools using for the formation of management decisions and the reconstruction of the Ukraine destroyed infrastructure. A diagram of the management tools using for the formation of management decisions concerning the reconstruction of the Ukraine destroyed infrastructure is constructed. The scientific novelty of the study is the proposal to apply the management tools for enterprises in force majeure conditions at any stage of the military and political situation in the country, taking into account the transitions from one stage of military and political conditions to another and the readiness of enterprises for their application. The practical value is that the article proposes management tools for assessing enterprise’s state and further making management decisions regarding business partnerships, in particular, in contracting works with state and local government bodies regarding the reconstruction of destroyed infrastructure in Ukraine at any stage of the country's military and political situation. This prism of considering the problem and finding ways to solve it will ensure a reliable perspective of partner business relations and their transparency, which will meet the requirements of the world's leading business practice.